Foundational biogeography: Vegetation of the Great Smoky Mountains (Ecological Monographs, 26: 1–80, 1956), by Robert H. Whittaker. (February 2020) - Malanson, George P; Peet, Robert K
A seminal paper in biogeography is reviewed. Whittaker's 1956 paper in Ecological Monographs introduced gradient analysis as a conceptual framework. This approach replaced community classification as the preferred methodology among US ecologists and biogeographers. It later developed into the foundation for species distribution modeling. Although the paper underlies a continuing rift between US and European scientists, both groups recognize its importance for relating ecological processes to geographical patterns.